Assessing Ideal Lip Anatomy Through Photogrammetry: Implications For Facial Reconstruction In Indonesia - Samsarga, Gede Wara; Sudarsa, Shita Diwyani; Suyata, Astrinita Lestari; Bertha Kawilarang; Valentin, Violetti; Gera, Luh Putu Mettary Yasoda (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Background : Anthropometry is a non-invasive, inexpensive, and objective method for evaluating orofacial morphology. This method has clinical applications in myofunctional assessment and therapy. Photogrammetry is a reliable and accurate method for measuring certain facial dimensions. In Indonesia, to date there has been no research that has conducted a photogrammetric evaluation of lip anthropormetry. Method : This study was conducted at the Faculty of Medicine, Udayana University which began in May to October 2024 with research subjects, namely 90 first-year undergraduate medical students, Faculty of Medicine, Udayana University. Data in the form of anthropometry, race, history of congenital abnormalities, facial trauma, siliconoma, age, gender and smoking were recorded and then analyzed. Result : The results of the analysis of lip anthropometry based on gender showed a significant difference in lower lip height, where in women the average was 3.25 (0.36) and in men 3.01 (0.30), with a p value of 0.001. Likewise, the lower lip height was found to be significantly different with a p value = 0.003. Upper vermilion height in women was 1.51 (0.35) while in men it was 1.36 (0.25), these results were statistically significant (p value = 0.041). However, the comparison of lower vermillion did not show any significant difference between the two groups. Cutaneous lower lip and philtrum width were also significantly different with p values of 0.004 and 0.015, respectively. Conclusion: The results of this study are expected to provide an overview of the analysis of anthropometric measurements of the lips using the photogrammetry method as basic data for measuring ideal lip anatomy in the field of facial reconstruction in Indonesia. Keywords: Anthropometric Measurement Of The Lip; Photogrammetry; Facial Reconstruction